Invoking International Human Rights Law To Prevent Statelessness Of International Refugee Children Born In Indonesia - Feby Dwiki Darmawan; Nur Heriyanto, Dodik Setiawan (Universitas Islam Indonesia, 2023)
The right to a nationality is an essential human right. The importance of having a nationality lies in the fact that it is a necessary condition for the protection and enjoyment of certain basic human rights. Consequently, the failure to fulfil the right of a child to get citizenship will have an impact on the fulfillment of their basic rights. This study explores the urgency of granting citizenship status for the statelessness of international refugee children born in Indonesia, and Indonesia’s responsibility to fulfill the right to a nationality for International Refugee children born in Indonesia under International Human Rights Law. This type of research is normative research using statutory and conceptual approaches. The results of this study indicate that, under international human rights law, everyone has the right to have citizenship and be recognized by their nationality from birth, including children born to refugees. Citizenship status in a person has become a practical prerequisite to be able to obtain respect, protection, and optimal fulfillment of human rights. Indonesian laws and regulations provide two approaches to obtaining citizenship status for refugee children born in Indonesia. The first solution is to prevent citizenship through positive law, and the second solution is to provide citizenship through naturalization. It is hoped that the Indonesian government will be proactive in fulfilling its obligation to provide Indonesian citizenship rights in refugee children’s best interests, and the Indonesian government is expected to ratify the 1954 and 1961 Refugee Conventions.Keywords: Human Rights, Right to a Nationality, Citizenship, Stateless. Mengundang Hukum Hak Asasi Manusia Internasional Untuk Mencegah Kewarganegaraan Terhadap Anak Pengungsi Internasional yang Lahir Di Indonesia AbstrakHak atas kewarganegaraan adalah hak asasi manusia yang esensial. Pentingnya memiliki kewarganegaraan terletak pada kenyataan bahwa itu adalah syarat yang diperlukan untuk perlindungan dan penikmatan hak asasi manusia tertentu. Konsekuensinya, tidak terpenuhinya hak anak untuk mendapatkan kewarganegaraan akan berdampak pada pemenuhan hak dasarnya. Kajian ini mengeksplorasi urgensi pemberian status kewarganegaraan bagi anak pengungsi internasional yang lahir di Indonesia yang tidak berkewarganegaraan, dan tanggung jawab Indonesia untuk memenuhi hak kewarganegaraan bagi anak Pengungsi Internasional yang lahir di Indonesia berdasarkan Hukum Hak Asasi Manusia Internasional. Jenis penelitian ini adalah penelitian normatif dengan menggunakan pendekatan statutoria dan konseptual. Hasil penelitian ini menunjukkan bahwa, berdasarkan hukum hak asasi manusia internasional, setiap orang berhak memiliki kewarganegaraan dan diakui kewarganegaraannya sejak lahir, termasuk anak yang lahir dari pengungsi. Status kewarganegaraan pada diri seseorang telah menjadi prasyarat praktis untuk dapat memperoleh penghormatan, perlindungan, dan pemenuhan hak asasi manusia secara optimal. Peraturan perundang-undangan Indonesia memberikan dua pendekatan untuk memperoleh status kewarganegaraan bagi anak-anak pengungsi yang lahir di Indonesia. Solusi pertama adalah mencegah kewarganegaraan melalui hukum positif, dan solusi kedua adalah memberikan kewarganegaraan melalui naturalisasi. Pemerintah Indonesia diharapkan proaktif dalam memenuhi kewajibannya untuk memberikan hak kewarganegaraan Indonesia untuk kepentingan terbaik bagi anak-anak pengungsi, dan pemerintah Indonesia diharapkan dapat meratifikasi Konvensi Pengungsi tahun 1954 dan 1961.Kata kunci: Hak Asasi Manusia, Hak atas Kewarganegaraan, Kewarganegaraan, Tanpa Kewarganegaraan.